Penggunaan Mendeley Bagi Mahasiswa STKIP Hatta-Sjahrir untuk Mengelola Referensi Ilmiah - Risnawati Umar; Ariestha Widyastuty Bustan; Muhammad Miftah Sabban (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Producing scientific work has become an obligation for students at a university since 2012. So the ability to manage scientific references, especially the use of applications in managing references is very necessary to support the writing of a scientific paper. Some applications that are specifically used to manage references are very easy to obtain, one of which is Mendeley. However, based on observations, most STKIP Hatta-Sjahrir students have not been able to use the Mendeley application. Even some of them do not know what Mendeley is. As a result, students still write references in a paper manually. Based on these problems, this training activity aims to introduce the Mendeley application and teach how to use the application. This training method is divided into three stages, namely the preparation stage, the implementation/practice stage, and the evaluation stage. This activity was attended by 15 students from various study programs at STKIP Hatta-Sjahrir. The results of the evaluation showed that participants were able to use the Mendeley application and felt that writing references and the citation process had become easier.